2021
DOI: 10.1021/acs.jmedchem.0c02081
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Disclosure of CVN424, a Potent and Selective GPR6 Inverse Agonist for the Treatment of Parkinson’s Disease: Discovery, Pharmacological Validation, and Identification of a Clinical Candidate

Abstract: Parkinson's disease (PD) is a chronic and progressive movement disorder with the urgent unmet need for efficient symptomatic therapies with fewer side effects. GPR6 is an orphan G-protein coupled receptor (GPCR) with highly restricted expression in dopamine receptor D2-type medium spiny neurons (MSNs) of the indirect pathway, a striatal brain circuit which shows aberrant hyperactivity in PD patients. Potent and selective GPR6 inverse agonists (IAG) were developed starting from a lowpotency screening hit (EC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…To reduce RNA degradation all nuclei samples were sorted at 4 °C and stored at −80 °C, before being processed for RNA extraction. RNA quality was assessed as previously described ( Sun et al, 2021 ). Gene expression quantification was performed with htseq-count v 0.6.1p1 using a custom annotation file to be able to quantify reads in both exons and introns of RefSeq genes.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce RNA degradation all nuclei samples were sorted at 4 °C and stored at −80 °C, before being processed for RNA extraction. RNA quality was assessed as previously described ( Sun et al, 2021 ). Gene expression quantification was performed with htseq-count v 0.6.1p1 using a custom annotation file to be able to quantify reads in both exons and introns of RefSeq genes.…”
Section: Methodsmentioning
confidence: 99%
“…It has been hypothesized that antagonism of this receptor provides a compensatory inhibition to the hyperactivity of the indirect pathway resulting from dopamine depletion. Preclinical studies using rat models have shown that CVN424 restores the normal basal ganglia circuitry and improves motor behavior in vivo [ 166 ]. A Phase 2 trial involving 135 PD patients with motor fluctuations is currently underway to evaluate the compound’s safety and efficacy (NCT04191577) [ 167 ].…”
Section: Motor Fluctuationsmentioning
confidence: 99%
“…GPR6 is a constitutively highly active G-protein coupled receptor 33,34 . This receptor is mainly expressed in mammalian brain, specifically striatum and hypothalamus, with very low expression at peripheral level.…”
Section: Resultsmentioning
confidence: 99%